STUDENTS’ READING STRATEGIES IN COMPREHENDING ACADEMIC READING: A CASE STUDY IN AN INDONESIAN PRIVATE COLLAGE - Fitriana, meida (International Journal of Language Education, 2018)
This study was intended to find out the certain strategies which were used by low level and high level English proficiency students in comprehending academic reading and the aspects which influence students’ reading comprehension. The methods of the research used a qualitative approach based on the theory of case study. The data were collected by using interviews, documentary studies and questionnaire. The data were analyzed using data reduction, data display and conclusion drawing. The results of this study showed different strategies using between low and high proficiency students. Moreover, the result also showed that there are five aspects which influence students’ reading comprehension such as, motivation, linguistics competence, interest, characteristic of the text and the last is environment role. Key words: Reading strategies, comprehension and academic reading